Key Capabilities for Successful Lean Implementation A study at an innovative start-up company in Sweden - Abdullahi, Flona; Karacan, Elif (My University, 2024)
Lean emphasizes waste reduction, continuous improvement and customer focus and has evolved from its origins in operational shop floor manufacturing to more of a socio-technical approach. Today, the deployment of lean is leaning towards a strategic perspective, where the approach is more management focused, shaping the strategy, culture and objectives of the organization. Implementing lean in an innovative environment is a newer concept that is perceived as both beneficial and challenging. The advantages of such an implementation includes enhanced efficiency and waste reduction, faster time-to-market, focus on customer value, continuous improvement and scalability. The challenges that come with the innovative environment involves the higher levels of uncertainty, resource constraints, rapid change, culture resistance, lack of historical data and balancing creativity with efficiency. When adapted correctly, lean can offer substantial benefits in terms of efficiency and scalability. This study aims to bridge gaps between the current state of an innovative startup and identified success factors for lean implementation. It explores how innovative startups must adapt to incorporate lean practices, focusing on essential success factors. Key challenges are identified, and success factors are suggested to address these challenges, with significant focus on cultural aspects. A qualitative study has been carried out at the company, and a total of 13 interviews has been conducted. The findings suggest several critical success factors that need to be present to implement lean successfully. These include leadership, culture and communication, human resources and training, customer focus, project management, strategy and targets, recognition and rewards, financial capabilities and lean methods and tools. The results from these suggest strategies that align with the key factors to foster optimal conditions for lean implementation. Innovative startups are recommended to implement structured HR programs for employee development, establishing clear communication channels, maintaining clear objectives and defined processes, and integrating customer feedback into product development.
Keywords: Lean; Start-up; High growth company; Lean methodology; High-tech company; Innovation; Innovative; Strategy; Change; Management